CONCEPTUAL BASICS OF TECHNOLOGICAL DEVELOPMENT AS A FACTOR FOR EXCESSING THE PROBLEM OF GLOBAL INEQUALITY - OLIYNYK, Kyrylo (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The purpose of the article is to establish the theoretical interdependencies between technological development and the problem of worsening inequality. It has been established that technological development is the result of a set of managed purposeful actions involving a change in technological structures, which leads to a change in the forms of manifestation of national, international and global inequality. Macro-level theories and models identify the non-neutral direction of technological change and describe the way in which the introduction of new technologies creates a demand for high-skilled labor, which contributes to an increase in the productivity of labor and capital, which finds expression in the widening of the wage differential between high-skilled and low-skilled workers, and in as a result, it increases manifestations of national inequality and international inequality. A number of meso-level theories consider the mechanisms of influence of sociotechnical regimes and technological transitions on social development, exploring the ways in which changes in technology, social practices, institutions, and market mechanisms can reduce manifestations of inequality. Accordingly, these theories lay the foundations for rethinking the neoclassical interpretation of the concept of "justice", and enable consideration of innovations not only from the standpoint of sustainable development, but also of inclusive growth, when innovations contribute to the achievement of more "fair" results, rather than increasing inequality. Among meso-level theories, two directions can be conventionally distinguished: (1) multi-level perspective research for describing and analyzing long-term transition processes and understanding how political initiatives can support transitions; (2) strategic niche management (strategic niche management), which assumes that sustainable innovative development is facilitated by the creation of technological niches or "protected spaces" that allow experimenting with the introduction of new technologies (experiments with new socio-technical configurations) and leveling negative side effects. Therefore, the meso-level theories are adaptive for the analysis of innovative policy, and allow to assess in advance its probable impact and to develop new institutional levers of influence on socio-economic development. Micro-level theories do not explain the interdependence of technological development and inequality, but focus on studies of micro-processes that affect the dynamics of innovations and their diffusion, resulting in technological development as such, regardless of countries or regions. Determining the impact of technology development on inequality is a complex and controversial process, and involves: (1) establishing a relationship between technology and economic growth (a certain outcome), when productivity is defined as a measure of production efficiency (i.e., an increase in technological capabilities, that is, a country's ability to acquire , learn, spread and apply modern technologies, leads to economic growth); (2) establishing a link between technology and equalization of opportunity (in a fair institutional environment, technology can reduce inequality by equalizing basic conditions, such as access to electricity or educational services).
Keywords: inequality; global inequality; global transformations; technological development; digital transformations; innovation; regulation; institutional environment